Prevalence and determinant of early childhood caries among the children attending the Anganwadis of Wardha district, India - Abhay M Gaidhane; Manoj Patil; Nazli Khatib; Sanjay Zodpey; Quazi Syed Zahiruddin (Wolters Kluwer Medknow Publications, 2013)
Background: Dental caries is one of the most common chronic diseases of early childhood. Dental problems in early childhood have been shown to be predictive of future dental problems, growth and development by interfering with comfort, nutrition, concentration, and school participation. Aim: To find out the prevalence of Early childhood caries (ECC) among the children attending the Anganwadis of Wardha district, to determine the feeding habits and their relationship to early childhood caries. Materials and Methods: Community-based cross-sectional study among the selected Anganwadis children of 2-5 years of Wardha district. Result: A total 330 subjects, 105 children were found to be having ECC, 47 (30.92%) males and 58 (32.58%) females. Total 215 children belonged to 43-60 months age group. Out of these, 72 (33.48%) children were having ECC. A significant association was found between the history of bottle-feeding and ECC (P = 0.0218). Prevalence of ECC was more among those who were bottle-fed than those who were not bottle-fed. Conclusion: Future health promotion and education programs in Anganwadis should include oral health issues and the risk factors for ECC, and its consequences should be addressed. Public-funded oral health program should be started and targeted at children from lower socioeconomic status. Effective strategies should be developed to promote use of brush and paste for cleaning teeth and discouraging inappropriate bottle-feeding, discouraging on demand consumption of chocolates and sugars.